Urban sustainability assessment: An analysis of how weighting and aggregating coefficient system was used in the development of SUCCEED assessment tool for developing countries - Momoh, Job; Ige, Olubisi; Seidu, Rafiu; Ogbenjuwa, Lucy; Young, Bert; Ibraheem, Yusuf (Frontiers in Built Environment, 2024)
The development of a weighting and aggregating coefficient system used in urban sustainability assessment tools is a process that needs well-defined procedures using a series of steps, methodology, and a systematic approach in its development. The development of assessment tools has been successful in developed countries but developing countries would need to have a structured process that will assist in the development of an assessment tool that is tailored to its environs. This paper aims to understand the various weighting and aggregating coefficient systems employed in the development of sustainability assessment tools. Alongside using these findings to understand how these weighting and aggregating coefficients can be adopted in the development of sustainability assessment tools for developing countries based on their differences, advantages, and disadvantages. Qualitative Content Analysis based on a systematic review of existing literature was used in this study to understand various weighting and aggregating coefficients. It is imperative to note that this research will focus on how assessment tools are developed with a clear focus on sustainability assessment weighting and aggregating. The study also further analyses how a case study SUCCEED (Sustainable Composite Cities Environmental Evaluation and Design Tool) has benefited from the adoption of equal weighting and additive aggregation methods based on validation carried out. The findings of this research show that the selection of weighting and aggregating systems is defined by the relevance, importance, and purpose of the assessment tool. It also develops a guide/recommendations on the process utilised in the development of assessment tools for developing countries.